Pattern Recognition in Bioinformatics 4th IAPR International Conference, PRIB 2009, Sheffield, UK, September 7-9, 2009. Proceedings - Kadirkamanathan, Visakan.; Sanguinetti, Guido.; Girolami, Mark.; Niranjan, Mahesan.; Noirel, Josselin. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the Fourth International Workshop on Pattern Recognition in Bioinformatics, PRIB 2009, held in Sheffield, UK, in September 2009. The 38 revised full papers presented were carefully reviewed and selected from numerous submissions. The topics covered by these papers range from image analysis for biomedical data to systems biology. The conference aims at crating a focus for the development and application of pattern recognition techniques in the biological domain.